The effect of infiltrant choice on the microstructure and mechanical properties of Rapidsteel2 - Uzunsoy, D; Chang, ITH (ELSEVIER SCIENCE BV, 2005)
At present, the research on the Rapidsteel produced using Selective Laser Sintering (SLS) method and infiltration process is mainly focused on the production of the parts with high accuracy and definition, very little effort has been devoted on the microstructural development and mechanical properties of this material. This paper offers a comparative evaluation of the microstructure and mechanical properties of Selective Laser Sintered (SLS) Rapidsteel(2.0) processed using three different copper alloys. Standard bronze infiltrant has been replaced with high tensile brass and magnesium aluminium bronze in order to improve the overall mechanical properties of Rapidsteel(2.0). The processing atmosphere had also a significant effect on the microstructure and mechanical properties of Rapidsteel(2.0). The parts debound under hydrogen and sintered/infiltrated under argon atmosphere. The microstructure of Rapidsteel consisted of stainless steel particulate surrounded with bronze infiltrant. Small amount of carbide precipitates (M23C6) were found after infiltration. The tensile fracture strength was found to increase in the order of high tensile brass
Keywords: stainless steel powders; infiltrants; sintering and infiltration; mechanical properties; metallography; SINTERING PROCESS; Materials Science; Physics